Identification of ‘Yongtai’ bayberry’s parents and analysis of their genetic variation by single nucleotide polymorphism markers - CHEN Fangyong; HU Dan; YAN Bangguo; NI Haizhi; WANG Yin (浙江大学学报. 农业与生命科学版, 2020)
In order to study the genetic relationship and genetic mechanism of ‘Yongtai’ and related nine bayberry (Myrica rubra) accessions, the methods of genomic re-sequencing and phylogenetic tree construction of core single nucleotide polymorphism (SNP), etc. were used, and also 4 025 core SNP markers were developed for further genetic and breeding research. The results calculated by genetic similarity (GS) showed that the GS between ‘Yongtai’ and ‘Yingsi’ was 0.997 83. Moreover, ten bayberry accessions were divided into two groups by phylogenetic tree construction analysis of SNP. ‘Heijing’, ‘Dong’aozaomei’, ‘Wuzi’, ‘Biqi’, ‘Muye’ were grouped together, and ‘Zaodamei’, ‘Zaojia’, ‘Ruansi’, ‘Yongtai’ and ‘Yingsi’ were grouped together, where ‘Yingsi’ and ‘Yongtai’ were gathered into a branch. At the same time, there were significant differences between ‘Yongtai’ and its parents in leaf size, leaf margin, leaf vein and fruit flavor. Through comparison and annotation of ‘Yongtai’ and the reference genome, a total of 4 660 differential genes were obtained. In conclusion, the significant morphological variation in leaves and fruits of ‘Yongtai’ may be attributed to the transition and transversion of SNP and the mutation of nucleotide sequence. So ‘Yongtai’ not only has the basic traits of its parent ‘Yingsi’, but also has its typically morphological traits as large leaves and large fruits.